An introduction to West Indian poetry - Breiner, Laurence A. (Cambridge University Press, 1998)
"This introduction to West Indian poetry is written for readers making their first approach to poetry in English written in the Caribbean. It offers a comprehensive literary history from the 1920s to the 1980s, with particular attention to the relationship of West Indian poetry to European, African, and American literature. Close readings of individual poems give detailed analysis of social and cultural issues at work in the writing. Laurence Breiner's exposition speaks powerfully about the defining forces in Caribbean culture from colonialism to resistance and decolonization. This book will be invaluable on courses in literature, history, Caribbean studies, cultural studies, and post-colonialism."--Jacket